Sectoral interlinkages in global value chains: Spillovers and network effects - Erik Frohm; Vanessa Gunnella (European Central Bank (ECB), 2017)
This paper studies the role of global input-output linkages in transmitting economic disturbances in the international economy. Our empirical results suggest that these sectoral spillovers are both statistically significant and of economic importance. We also provide evidence that it is not the interlinkages per se that matter for the international transmission but rather the presence of global hub sectors that are either large suppliers or purchasers of other sectors' inputs. When the links between these sectors and the rest of the global value chain are severed, the spillovers diminish strongly and eventually become statistically insignificant. This highlights the importance of the structure of the network for enabling spillovers and the prominent role played by hub sectors in the global economy.
Keywords: E30; E32; F44; F62; 330; input-output linkages; networks; spillovers; global value chains